Pengaruh Kecerdasan Emosional, Partisipasi Guru dalam Forum Ilmiah, Keyakinan Diri (Self Efficacy), dan Motivasi Kerja Terhadap Kinerja Guru Matematika - Herawaty, Dewi (UIN Sunan Ampel Surabaya, 2016)
This research aims to understand the direct effect of emotional intelligence, teacher participation in scientific forum, self efficacy, and motivation to work performance math teacher. The research was conducted by survey method and sample were 100 math teachers of 680 math teachers in the junior high schools of Bengkulu Province. The data was collected through a likert scale questionnaire technique. The quantitative data were processed by the path analysis. The result were direct effect of: 1)  emotional intelligence, teacher participation in scientific forums, and self efficacy influence on job motivation of teachers; 2) emotional intelligence, teacher participation in scientific forums directly impact the self efficacy of teachers; and 3) emotional intelligence, teacher participation in scientific forums, self efficacy and motivation to directly influence the performance of a teacher of mathematics.